Numerical study of critical straight, frown, and chevron incisions in small incision cataract surgery - Han, Yang; Qi, Nan (Frontiers in Bioengineering and Biotechnology, 2023)
When an intraocular lens (IOL) injector is inserted through a pre-cut corneal incision (e.g., an empirical size of 2.2 mm) during small incision cataract surgery, uncontrollable tearing to the corneal tissue may occur, which is highly associated with the incision shape, size, and location. The goal of this numerical study was to investigate the optimal incision scheme amongst three typical shapes, i. e. straight, frown, and chevron incisions using mechanical modelling and finite element analysis. Assuming that the damage is caused by the tissue fracture at the incision tips and is governed by the classical energy release rate(ERR) theory which compares the current ERR value subject to IOL injection and the material's intrinsic parameter, critical ERR G c . It was found that for chevron incisions, the incision shape with an angle of 170 • was superior which induced minimal ERR value, while for frown incisions, the shape with a central angle of 6 • was optimal. Both chevron and frown incisions could allow a larger size of injector to inject through than a straight pre-cut. In particular, the frown incision performed the best due to its lowest corresponding ERR and easy operation. It was also observed that regions where the embedded fibrils are most dispersed and exhibit high isotropy were favourable. If necessary, the chevron incision was recommended to be more aligned with the direction exhibiting a larger modulus, for example, along the circumferential direction near the limbus. This study provides useful knowledge in operation design and a deep insight into mechanical damage to corneal wounds in small incision cataract surgery.